2022
DOI: 10.1007/s12232-022-00403-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing work-satisfaction of global garments supply chain workers in Bangladesh

Abstract: The purpose of this study is to assess different factors under the Bangladesh labour legislation for promoting work-satisfaction of the global garment workers in Bangladesh. A convenient sampling technique was used for collecting 208 employee responses through a five-point Likert scale structured questionnaire. The respondents were garments-manufacturing industry workers working in three hot spots known as towns of Savar and Ashulia (Dhaka District) and Gazipur Sadar (Gazipur District). The survey was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The results further suggested that overall job satisfaction was pointedly higher among the satisfied respondents than that of the dissatisfied respondents. Several investigators, i.e., Asikullah [ 22 ]; Shan et al [ 73 ]; Syed and Mahmud [ 19 ]; Arslan [ 80 ]; Hechanova and Manaois [ 81 ]; Shi, Gordon and Tang [ 89 ] also found a significant impact of professional aspects on the overall job satisfaction of the respondents, which inveterate the outcomes of the present study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The results further suggested that overall job satisfaction was pointedly higher among the satisfied respondents than that of the dissatisfied respondents. Several investigators, i.e., Asikullah [ 22 ]; Shan et al [ 73 ]; Syed and Mahmud [ 19 ]; Arslan [ 80 ]; Hechanova and Manaois [ 81 ]; Shi, Gordon and Tang [ 89 ] also found a significant impact of professional aspects on the overall job satisfaction of the respondents, which inveterate the outcomes of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Job security, working conditions, having high compared earnings, functional flexibility, and high involvement management practices are job and organizational characteristics that are positively related to job satisfaction [ 77 ]. Syed and Mahmud [ 19 ] found that the three additional factors—salary amount, prompt payment of salaries, and employee advancement policies—also have a big impact on workers’ satisfaction. The relationship between job satisfaction and the workplace, employees are more likely to enjoy their work when they feel comfortable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations